Fologram tool to improve spatial skills in Interior Architecture students - Chávez, Alicia (2023)
The objective of this article was to demonstrate the effects of the application of the fologram tool on the spatial abilities of the students of Interior Architecture of the Toulouse Lautrec School of Higher Education, the methodology had a quasi-experimental design and the type of applied research, the sampling It was not probabilistic, the sample was made up of 32 students, who made up the experimental and control group, the technique used was the survey and a questionnaire was applied for the pre and post-test, for the experiment sessions were developed using the fologram tool, since This software helped students to understand, manipulate data so that they can visualize and distinguish objects in two and three dimensions. Regarding the result, a significance of 0.001 was obtained, which indicated that the application of the augmented reality software fologram has effects on the improvement of the spatial ability of Toulouse Lautrec students, since it allowed them to consolidate the construction of spatial ability.